Development of an Improved 3D in vitro Intestinal Model to Perform Permeability Studies of Paracellular Compounds - Macedo, Maria Helena; Martinez, Elena; Barrias, Cristina C.; Sarmento, Bruno (Frontiers in Bioengineering and Biotechnology, 2020)
The small intestine is the primary site of drug absorption following oral administration, being paramount the proper monitoring of the absorption process. In vitro tools to predict intestinal absorption are particularly important in preclinical drug development since are less laborious, cost-intensive, and raise less ethical considerations compared to in vivo studies. The Caco-2 model is considered the gold-standard of in vitro intestinal models regarding the prediction of absorption of orally delivered compounds. However, this model presents several drawbacks, such as expression of tighter tight junctions, not being suitable to perform permeability of paracellular compounds. Besides, cells are representative of only one intestinal cell type, without considering the role of non-absorptive cells on the absorption pathway of drugs. In the present study, we developed a new 3D intestinal model to bridge the gap between in vitro tools and animal studies. Our 3D model comprises a collagen layer with human intestinal fibroblasts (HIF) embedded, mimicking the intestinal lamina propria and providing 3D support for the epithelium, composed of Caco-2 cells and mucus producing HT29-MTX cells. The optimization of the collagen layer with HIF was performed testing different collagen concentrations and different HIF seeding densities and it was observed that a collagen concentration of 6 mg/mL and a cell seeding density of 1x105 HIF/mL were optimal to avoid collagen contraction before day 14, maintaining HIF metabolically active inside the collagen disks during time in culture. HIF morphology and extracellular matrix (ECM) deposition were assessed and it was possible to see fibroblasts with their normal and healthy elongated shape, secreting fibronectin and laminin, and remodeling the collagen matrix. Regarding the epithelial layer, transepithelial electrical resistance (TEER) values decreased when cells were in the 3D configuration, comparing with the 2D analogs (Caco-2 and co-culture of Caco-2+HT29-MTX models), becoming more similar with in vivo values. The permeability assay with FITC-Dextran 4kDa showed that absorption in the 3D models is significantly higher than in the 2D models and that this is related not only with the TEER values, but also with the fact that cells behave more physiologically in the 3D models, having an impact in permeability.